The Effect of Working Conditions of Doctors on Their Burnout Levels - ERİŞ, Hüseyin (International Journal of Psychosocial Rehabilitation, 2020)
Burnout is a syndrome that is characterized by physical, emotional, and mental exhaustion that maintains with the emergence of consistent tiredness, desperation, hopelessness, and loss of self-respect emotions, causing troubles in someone’s work life or her/his relationship with other people. This study is carried out to determine the effect of working conditions of doctors working in Şanlıurfa on their burnout levels. Within this regard, a questionnaire is conducted to 257 out of 750 doctors from 3 public hospitals, one private hospital, and one university hospital in the city center of Şanlıurfa by using a simple random sampling method between 02.12.2019 and 25.01.2020. The emotional burnout levels of doctors are high, and they are not content with the working conditions. At the end of the research, it is found out that doctors experience burnout at a medium level, and there is a medium-level relationship between working conditions and burnout. As a result of the regression analysis, it is expected that the improvement in the working conditions of doctors causes to decrease the burnout level of them, thereby, an improvement in a general sense.